N-acetylcysteine in the Prevention of Contrast-induced Acute Kidney Injury: a Systematic Review and Meta-analysis of Randomized Controlled Clinical Trials - E. M. Mezhonov; Yu. A. Vyalkina; S. V. Shalaev (Столичная издательская компания, 2022)
Aim. To analyze the currently available published randomized controlled clinical trials to evaluate the effect of N-acetylcysteine on the incidence of contrast-induced acute kidney injury (CI-AKI).Material and methods. The meta-analysis was performed in accordance with the PRISMA guidelines based on a search of existing literature in the PubMed/MEDLINE database for the period from 2015 to 16 February 2022. Keywords included MeSH terms «acute kidney injury» or «contrast-induced nephropathy» or «AKI» or «CIN» and «contrast media» and «N-acetylcysteine». The RoB 2 tool was used to assess study bias.Results: When searching based on the initially selected statistics, 98 publications were identified, some of them were excluded from the analysis due to non-compliance with the inclusion criteria in this meta-analysis, 7 studies of unused sources of detection were ultimately selected, the total number of patients in the discovery was 10394.The results of the meta-analysis revealed that in patients treated with N-acetylcysteine CI-AKI developed with the same frequency as in patients who did not observe such therapy as a prophylaxis for this disease (odds ratio 1.06, 95% confidence interval 0.911.23, p=0.46).Conclusion. The use of N-acytelcysteine does not offer any advantage in reducing the incidence of CI-AKI compared with the administration of saline solutions (sodium bicarbonate or sodium chloride 0.9%) or placebo.